An evaluation of the healthcare costs of metastatic breast cancer: A retrospective matched cohort study. Issue 43 (29th October 2021) - Chen, Hsuan-Ming; Chen, Jin-Hua; Chiang, Shao-Chin; Lin, Yi-Chun; Ko, Yu
Abstract : Abstract: To determine the economic burden of metastatic breast cancer (MBC) in Taiwan, we conducted a national retrospective claim database analysis to evaluate the incremental healthcare costs and utilization of MBC patients as compared to their breast cancer (BC) and breast cancer free (BCF) counterparts. Data were obtained from the National Health Insurance Claim Database and the Taiwan Cancer Registry database between 2012 and 2015. All healthcare utilization and costs were calculated on a per-patient-per-month (PPPM) basis and were compared among groups using the generalized linear model adjusting for age group, residential area, and Charlson comorbidity index group. A total of 1, 606 MBC patients were matched to 6, 424 BC patients and 6, 424 BCF patients. The majority of overall MBC healthcare costs were attributed to outpatient costs (75.1%), followed by inpatient (23.2%) and emergency room costs (1.7%). The PPPM total healthcare costs of the MBC, BC, and BCF groups were TWD 7, 422, 14, 425, and 2, 114, respectively. The adjusted PPPM total healthcare cost ratio of MBC to BCF was 4.1. Compared to BCF patients, the patients receiving both human epidermal growth factor receptor 2-targeted therapy and endocrine therapy incurred 28.1 times PPPM total costs. The adjusted PPPM total healthcare cost ratio of recurrent MBC to BCF was 2.3, while the ratio was 12.2 in the de novo MBC group. Patients with MBC are associated with substantial economic burden, particularly in outpatient costs. The study findings could be useful for MBC-related economic evaluations and health resource allocation.